Social Factors and UFO Reports: Was the SARS-CoV-2 Pandemic Associated with an Increase in UFO Reporting? - Cockrell, R Chase; Murphy, Linda; Rodeghier, Mark (Journal of Scientific Exploration, 2023)
The ongoing SARS-Cov-2 pandemic had many drastic effects upon society beyond the illness and death it caused. Pandemic mitigation measures disrupted and altered behaviors related to social mobility, significantly increasing the time spent at home compared to the pre-pandemic period. Further, it was well documented that social anxiety and stress increased at a population level. Early in the pandemic there was speculation in the popular media that reporting of paranormal phenomena (e.g., UFOs, ghosts, etc.) increased due to factors associated with the pandemic. Past research on UFO/UAP reporting has theorized that increases are triggered by social factors, and so the pandemic provided a natural experiment to test these claims. To measure UFO reports we utilized two public databases of UFO reports for sightings in the United States, provided by the National UFO Reporting Center and the Mutual UFO Network. To estimate the impact of the pandemic we utilized two measures, one for social mobility and one for pandemic/disease severity. Google Community Mobility Reports provided a metric of social mobility for people who use Google Maps on their cellular telephone (i.e., amount of time spent at work compared to home), which we aggregated to a state level to estimate time spent at home. Second, we used new weekly SARS-CoV-2 cases and deaths, both absolute counts and per capita, which can be considered to be an indirect measure of anxiety and stress. We find that UFO reports did increase in 2020 compared to 2019 (p<0.001 for both databases); however, the level of UFO reporting had little to no association with the various pandemic-related measures, offering no support for hypothesized social factors that influence reporting. A complicating factor in UFO reporting is the start in 2019 of Starlink satellite launches. These launches include up to 60 small satellites at once, and so are very distinctive and often easily visible. As a result, many people report these as UFOs. We coded and removed these reports from the sighting databases, and the filtered data similarly have no association with the pandemic-related factors. Further, with Starlink reports removed, there was no increase in sightings in 2020 compared to 2019. Our results contribute to an understanding of large-scale factors that impact the reporting of paranormal events, especially timely given the renewed public and government focus on the UFO phenomenon today.